Water on Atomically-Defined Cobalt Oxide Surfaces Studied by Temperature-Programmed IR Reflection Absorption Spectroscopy and Steady State Isotopic Exchange - Schwarz, Matthias; Mohr, Susanne; Hohner, Chantal; Werner, Kristin; Xu, Tao; Libuda, Jörg (Journal of Physical Chemistry C, 2018)
In this work, we investigate the interaction of water with three different atomically defined cobalt oxide surfaces under ultrahigh vacuum (UHV) conditions using time-resolved and temperature-programmed infrared reflection–absorption spectroscopy (TR-IRAS, TP-IRAS) in combination with isotopic exchange experiments. The three surfaces, CoO(100), CoO(111), and Co3O4(111), are prepared in form of well-ordered films on Ir(100). Very different behavior is observed on the three surfaces, both with respect to D2O adsorption and desorption. On CoO(100), water adsorbs molecularly. It forms extended ice clusters even at low adsorption temperature (200 K) and which desorb molecularly at 200 K (Ea,des ∼ 60 kJ·mol–1). A very small amount of defect sites is observed at which D2O dissociates and forms strongly bound OD groups. On CoO(111), the interaction with ordered facets is very weak and no adsorption occurs at these sites at 200 K. The CoO(111) films expose, however, a higher density of defects as compared to the CoO(100) films, at which D2O dissociates and forms strongly bound OD species with desorption temperatures of 455 ± 10 and 620 ± 10 K, respectively. In contrast to the above cases, water interacts strongly with the Co3O4(111) surface. At 200 K, D2O dissociates readily and forms a partially dissociated (D2O)n(OD)m network. With increasing temperature, the (D2O)n(OD)m network breaks up into (D2O)n(OD)m clusters the size of which decreases with increasing temperature. Desorption of molecular D2O occurs over a broad temperature range from 210 to 470 K (Ea,des ∼ 60 to ∼ 140 kJ·mol–1). Above 470 K, only isolated OD species reside on the surface which desorb at 540 ± 20 K. Isotopic exchange experiments with D2O and H2O on Co3O4(111) show that isotopic scrambling in the (D2O)n(OD)m clusters is slow in comparison to exchange with the gas phase and that the clusters are composed of distinct species that show different exchange rates with the gas phase. The structure-dependent differences regarding the interaction with D2O are rationalized in terms of the surface termination and coordination environment of the surface ions on the three different surfaces.
EAM Import::2019-03-12